(untitled) (Heritage, 2022)
The work deals with the artistic creations of Petar Djuza, a contemporary Serbian artist and university professor from Kosovo and Metohija.He, as a painter, opposed the persecution of the Serbian people from the area of Kosovo and Metohija in an artistic way in the eighties of the last century. The exodus experienced by the Serbs at that time was best expressed by the artist through his own creative expression.A representative example is the work Two headed forbids prayer (Dvoglavorušazabranjujemolitvu), from Djuza’s Hvostan art cycle.This artist’s cycle contained paintings of monumental dimensions that were mostly destroyed in his studio in Pristina in 1999.